Tajikistan Agricultural Sector Risk Assessment - Broka, Sandra; Giertz, Åsa; Christensen, Garry; Hanif, Charity; Rasmussen, Debra (World Bank, Washington, DC, 2016)
Agriculture is among the most risk-prone sectors in the economies of Central Asia. Production shocks from weather, pests and diseases and adverse movements in agricultural product and input prices not only impact farmers and agri-business firms, but can also strain government finances. Some of these risks are small and localized and can be managed by producers. Others are the result of more severe, exogenous shocks outside agriculture or outside the country, which require a broader response. Failure to respond adequately to these more severe risks leads to a perpetual cycle of ‘shock-recovery-shock’, which reinforces poverty traps and compromises long-term growth. The agriculture sector’s exposure to production and price risk is increasing. Climate change is increasing production risks in the short to medium-term by increasing the frequency and severity of droughts and floods and in the longer-term by reducing the availability of water for irrigation due to accelerated glacial melt. The modernization and commercialization of agricultural production and processing, which is critical for sector growth, also raises the sector’s exposure to price risk at a time of high volatility on international markets for agricultural commodities. An effective response to these risks requires a broader, more integrated approach to risk management than the current system of ex-ante, public sector activity associated with crop and livestock disease and ad hoc, ex-post emergency responses to local disasters. Measures to strengthen risk mitigation will need to be mainstreamed into sector development and investment programs, additional human and financial resources will need to be allocated to the public institutions responsible for ex-ante and ex-post risk management, and the potential for transfer (insurance) mechanisms will need to be clarified and developed where feasible. Given the limited human and financial resources available for public sector activity, a clear sense of the priorities for agriculture risk management is also required, together with a balanced view of the respective roles of public and private sector stakeholders.